Development of eggshell membrane as solid phase adsorbent for Cd(II), Pb(II) and Ni(II) coupled with flame atomic absorption spectrometry - Duangkum, Tanawat; Masawat, Prinya; Udnan, Yuthapong (Asian Health, Science and Technology Reports, 2012)
The aim of this study was to develop natural material for preconcentration of some heavy metals. In this research, the eggshell membrane (ESM) of hen and duck were studied in two types; natural and boiled ESM. Characterization of ESM by Fourier Transform Infrared spectroscopy (FT-IR) and Scanning Electron Microscope (SEM) demonstrated that the FT-IR spectra showed broad -OH stretching absorption band at 3419 cm-1 and C-H stretching at 2930 cm-1. The peaks observed at 1652 and 1534 cm-1 represented the amide I and II absorption bands, respectively. These functional groups could therefore capture metal ions. The SEM images of boiled hen and duck ESM showed that the membrane fibers were mostly destroyed. Due to the difficulty of preparation of natural hen ESM, the natural duck ESM (Dn-ESM) was selected as a preconcentration sorbent. The duck eggshell was collected from the biggest Thai dessert factory in Phitsanulok province only one place to reduce the contamination from raw materials. Dn-ESM was studied for preconcentration of Ni(II), Cd(II) and Pb(II) in batch method. The metals were determined by flame atomic absorption spectrometer. Under the optimum analytical conditions, the maximum adsorption of Ni(II), Cd(II) and Pb(II) on Dn-ESM were more than 90%. The recoveries of Pb(II) were in the range of 85 to 98% by desorption using 0.5 M HNOassisted acid digestion. Detection limits defined as three time of standard deviation of the blank were 0.015 mgL3. The recoveries of Ni(II) and Cd(II) were in the range of 83 to 92% and 90 to 100%, respectively, by using the ultrasound-1 for Ni(II), 0.002 mgL-1 for Cd(II) and 0.132 mgL-1 for Pb(II) with enrichment factors of 2.63 for Ni(II), 2.96 for Cd(II) and 2.47 for Pb(II) and relative standard deviations (RSD) were 6.6%, 5.1% and 5.1%, respectively. Ni(II) and Pb(II) were observed in the sample sites of Phitsanulok province and Phichit province. Fortunately, Cd(II) was not detected in Nan River in the Lower Northern of Thailand by the proposed method.